A comparative study of Faine’s criteria, modified Faine’s criteria, and microscopic serum agglutination test to diagnose the leptospirosis - Balakrishnan, Parthiban; Padmanabhan, Ramkumar; Pasupathy, Sekar; Sankaranarayanan, Balasubramanian (Indian Journal of Child Health, 2019)
Introduction: Leptospirosis is an important zoonotic infectious disease globally, caused by spirochetes from the genus Leptospira. The usefulness of Faine’s criteria and modified WHO Faine’s criteria 2012 for diagnosing human leptospirosis has turned out to be a valuable tool; however, limited studies have demonstrated the usefulness of these diagnostic methods in children. Objective: The objective of the study was to assess the performance characters of Faine’s and modified Faine’s criteria in diagnosing pediatric leptospirosis. Methods:This descriptive prospective observational study was done over a period of 2 years on children from 1 year to 12 years of age hospitalized for fever of more than 7 days duration with symptoms and signs suggestive of leptospirosis. Faine’s and modified Faine’s criteria were used in the diagnosis of leptospirosis, and the entire study population was tested by microscopic agglutination test (MAT). Results: A total of 91 children were included in the present study with the mean age of 5.4±1.41 years; out of which, 57 were boys and 34 weregirls. All had a fever of >39°C with myalgia (76%) and headache (69%). History of contact with the contaminated environment was present in 79% cases and 53% of cases had contact with animals. Out of 23 children diagnosed with leptospirosis using Faine’s criteria, 2 were MAT positive. Out of 68 children, who were not diagnosed with Faine’s criteria, 52 were MAT negative. Thirty-nine children were diagnosed by modified Faine’s criteria and 17 of them were MAT positive. Fifty-two children ruled out leptospirosis using modified Faine’s criteria; out of which, 51 children were MAT negative which was statistically significant. The sensitivity of 94.4% and specificity of 69.9% of modified Faine’s criteria to diagnosis leptospirosis were significantly higher than the sensitivity of 11.1% and specificity of 71.2% of Faine’s criteria. Conclusion: The modified Faine’s criteria potentially provide a better alternative to Faine’s criteria in the diagnosis of leptospirosis. Modified Faine’s criteria can be very useful to diagnose leptospirosis in the resource-poor settings where the gold standard tests to diagnose leptospirosis such as culture and MAT are not available.